Preparation method of copper-doped cerium oxide gas sensitive material, gas sensor and application

The preparation of copper-doped cerium oxide nanotube gas-sensitive materials through electrospinning-calcination solves the problem that H2S cannot be accurately detected in low oxygen environments in the prior art, and high sensitivity detection of H2S at lower operating temperatures is achieved, which significantly improves the response and selectivity of the material.

CN119551703APending Publication Date: 2025-03-04SUZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411713645.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Existing commercial semiconductor gas sensors cannot accurately detect trace amounts of H2S in low oxygen environments, and ceria materials have poor electrical conductivity, high operating temperature and poor gas selectivity.

Method used

Copper-doped cerium oxide nanotube gas-sensitive materials are prepared by electrospinning-calcination, which utilizes the oxygen storage performance and Cu doping effect of CeO2 to reduce the working temperature of the material and improve conductivity and gas selectivity.

Benefits of technology

Accurate detection of H2S at lower operating temperatures is achieved. The material maintains good response-recovery characteristics in a variety of oxygen content environments, with a 1.7-fold increase in response and significantly enhanced selectivity, which can achieve accurate detection of H2S in a low-oxygen environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551703A_ABST
    Figure CN119551703A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a copper-doped cerium oxide gas sensitive material, a gas sensor and application, the preparation method of the gas sensitive material comprises the following steps: adding cerium salt and copper salt into a mixed solution of ethanol and DMF or ethanol and deionized water, and stirring to form a transparent solution; adding PVP (Polyvinyl Pyrrolidone) into the solution, and stirring to form viscous liquid; performing electrostatic spinning on the viscous liquid to obtain nanofibers; and calcining the nano fiber to obtain the Cu doped CeO2 nano tube. According to the method, the in-situ Cu-doped CeO2 nanotube is prepared through electrostatic spinning-calcination, due to the oxygen storage performance and the Cu doping effect of CeO2, in the process of dynamically detecting the target gas H2S, the working temperature of the synthesized sensitive material is reduced, the good response-recovery characteristic can be kept in various oxygen content environments, and the sensitivity is high. And a new path is opened up for developing a novel metal oxide semiconductor gas sensor adapting to a complex environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method of a gas-sensitive material, a gas sensor and applications, and in particular to a preparation method of a copper-doped cerium oxide gas-sensitive material, a gas sensor and applications. Background Art

[0002] Hydrogen sulfide (H2S) is a colorless, toxic, flammable, corrosive, acidic, and foul-smelling gas. When high-concentration H2S is inhaled into the human body, it will paralyze the respiratory center and vasomotor center of the human body, causing serious consequences such as coma and suffocation. Low-concentration H2S can also irritate the human eyes and respiratory system. Therefore, it is of great significance to develop a high-performance gas sensor that can monitor trace amounts of H2S in real time.

[0003] Semiconductor gas sensors use the reaction between the target gas and the surface of the semiconductor material to cause changes in the semiconductor's electrical properties (resistance, current, etc.) to analyze the type and concentration information of the target gas. Gas-sensitive materials are the core part of semiconductor gas sensors. Currently, the gas-sensitive materials of commercial H2S sensors are mainly metal oxide semiconductors, including tin dioxide (SnO2), zinc oxide (ZnO), copper oxide (CuO), etc. Compared with other gas-sensitive materials (two-dimensional materials, conductive polymers, carbon nanotubes), etc., they have the advantages of good stability, high sensitivity, and fast response speed, and therefore have been widely used. With the improvement of people's safety awareness and the development of Internet of Things technology, higher performance requirements have been put forward for semiconductor gas sensors, including ultra-low detection limits, excellent resistance to environmental interference, and good selectivity.

[0004] However, currently commercial semiconductor gas sensors cannot be used for gas detection in low oxygen environments. For example, the standard test environment for Weisheng Technology's MQ136 hydrogen sulfide gas sensor is the oxygen content (21%) in a plain environment, and the oxygen content is required to be no less than 18%, otherwise it will affect the sensitivity and repeatability of the sensor. However, in high-altitude areas, manholes, low-oxygen fermentation workshops in factories, SF6 high-voltage cabinets and other environments, the oxygen content often does not meet the requirements of the sensor. The Chu Jifeng team of Xi'an Jiaotong University used commercial Figaro TGS2600, TGS2603, Winsen MP2, and MP503 sensors to detect H2S in an oxygen-free SF6 environment. The results showed that the sensor limit drift was serious and a regular response-gas concentration relationship could not be obtained (Electrical and Power Engineering (CEEPE), 26-28 April, 2024). Therefore, currently commercial semiconductor gas sensors cannot accurately detect H2S in low oxygen environments (oxygen content is less than 18%), and there is an urgent need to develop new gas-sensitive materials.

[0005] Cerium dioxide (CeO2) is expected to achieve accurate detection of H2S at different oxygen contents, but it faces problems such as poor conductivity, high operating temperature, and poor gas selectivity. 3+ / Ce 4+ The redox ion pair properties give it the ability to store oxygen. However, due to the wide bandgap (~3.4 eV) of CeO2 itself, its conductivity is poor. When used as a gas sensor, it often requires a higher operating temperature (greater than 300°C) to overcome the carrier sensing barrier inside the material. In addition, research reports have found that in addition to being more sensitive to H2S, cerium oxide also has a greater response to acetone, so its gas selectivity is poor. Summary of the invention

[0006] Purpose of the invention: The purpose of the present invention is to provide a method for preparing a copper-doped cerium oxide gas-sensitive material that can detect H2S in a low oxygen content environment at a relatively low operating temperature;

[0007] A second object of the present invention is to provide a gas sensor that can operate at a relatively low operating temperature and has a high gas selectivity;

[0008] The third object of the present invention is to provide the application of the copper-doped cerium oxide gas-sensitive material prepared by the above method.

[0009] Technical solution: The method for preparing the copper-doped cerium oxide gas-sensitive material of the present invention comprises the following steps:

[0010] (1) adding cerium salt and copper salt to a mixed solution of ethanol and DMF or ethanol and deionized water, stirring to form a transparent solution;

[0011] (2) adding PVP to the above solution and stirring to form a viscous liquid;

[0012] (3) electrospinning the viscous liquid to obtain nanofibers;

[0013] (4) Calcinate the nanofibers to obtain Cu-doped CeO2 nanotubes.

[0014] Wherein, in step (1), the molar ratio of Ce element to Cu element is 1:1 to 5:1.

[0015] Wherein, in step (1), the organic solvent is a mixed solution of ethanol and DMF, and the volume ratio of ethanol to DMF is 1:1 to 3:2.

[0016] Wherein, in step (2), the average molecular weight of the PVP is 1,300,000.

[0017] Wherein, in step (3), the parameters of the electrospinning are: the voltage applied to the needle is 18 kV, the distance between the needle and the spinning collector is 20 cm, and the syringe propulsion speed is 0.6 mL / min.

[0018] Wherein, in step (4), the calcination temperature is 400-600° C. and the calcination time is 2-4 hours.

[0019] Wherein, in step (4), the heating rate of calcination is 0.5 to 5°C / min.

[0020] The gas sensor of the present invention uses a gas sensitive material including the copper-doped cerium oxide gas sensitive material prepared by the above method.

[0021] The copper-doped cerium oxide gas-sensitive material prepared by the above method is used in detecting H2S gas.

[0022] Beneficial effects: Compared with the prior art, the present invention achieves the following significant effects:

[0023] (1) The present invention prepares in-situ Cu-doped CeO2 nanotubes by electrospinning-calcination. Thanks to the oxygen storage performance of CeO2 itself and the Cu doping effect, the working temperature of the synthesized sensitive material is reduced during the dynamic detection of the target gas H2S, and it can maintain good response-recovery characteristics under a variety of oxygen content environments, opening up a new path for the development of new metal oxide semiconductor gas sensors that adapt to complex environments. (2) The Cu-doped CeO2 nanotube gas-sensitive material obtained by the present invention is used to prepare a gas sensor. Under dynamic gas distribution test conditions, the experimental H2S detection limit of the Cu-doped CeO2 nanotube material is 100 ppb, the theoretical detection limit is 17.5 ppb, the optimal working temperature is 260°C, and the response to 4 ppm H2S is 7.4. Thanks to the Cu doping effect, more oxygen vacancies are created on the surface of CeO2 nanotubes, thereby improving the conductivity of the material and increasing the gas adsorption sites, making the optimal Cu-doped CeO2 nanotube material (Ce / Cu-5) 4.8% lower in optimal operating temperature and 1.7 times higher in response than pure CeO2. In addition, the Ce / Cu-5 material exhibits better selectivity. (3) Thanks to the oxygen storage properties of CeO2, under dynamic test environments with different oxygen contents, the Cu-doped CeO2 nanotube material exhibits almost consistent and rapid H2S adsorption-desorption behavior, with good repeatability, and can achieve accurate H2S detection in low-oxygen environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 XRD patterns of materials prepared in Examples 1-3;

[0025] Figure 2This is the SEM image of Cu-doped CeO2 nanotubes (Ce / Cu-5) prepared in Example 1;

[0026] Figure 3 Element distribution diagram of Cu-doped CeO2 nanotubes (Ce / Cu-5) prepared in Example 1;

[0027] Figure 4 Raman spectra of CeO2 and Ce / Cu-5 materials prepared in Comparative Example 1 and Example 1;

[0028] Figure 5 The sensors assembled from CeO2 and Ce / Cu-5, Ce / Cu-2, and Ce / Cu-1 prepared in Comparative Example 1 and Examples 1, 2, and 3 responded at different operating temperatures;

[0029] Figure 6 The responses of the sensors assembled with CeO2 and Ce / Cu-5 prepared in Comparative Example 1 and Example 1 to different gases;

[0030] Figure 7 The dynamic response curve of the sensor assembled with Ce / Cu-5 prepared in Example 1 to different concentrations of H2S;

[0031] Figure 8 Response / recovery time of the Ce / Cu-5 assembled sensor prepared in Example 1;

[0032] Fig. 9 Dynamic resistance curve of the sensor assembled with Ce / Cu-5 prepared in Example 1 to H2S at different oxygen contents;

[0033] Fig.10 The response values ​​of the sensor assembled with Ce / Cu-5 prepared in Example 1 to H2S at different oxygen contents;

[0034] Fig.11 Response / recovery time of the Ce / Cu-5 assembled sensor prepared in Example 1 to H2S at different oxygen contents. DETAILED DESCRIPTION

[0035] The present invention is described in further detail below.

[0036] Example 1

[0037] A method for preparing a copper-doped cerium oxide gas-sensitive material, the specific steps are as follows:

[0038] (1) Preparation of nanofibers by electrospinning

[0039] First, prepare a mixed solution of ethanol and dimethylformamide (DMF), in which the volume ratio of ethanol to DMF is 3:2. Take 0.6g of cerium nitrate hexahydrate (Ce(NO3)2·6H2O) and 0.067g of copper nitrate trihydrate (Cu(NO3)2·3H2O), add 10mL of the prepared mixed solution of ethanol and DMF, and then stir magnetically at room temperature for 30 minutes at a speed of 1000r / min to fully dissolve the material and finally form a blue transparent solution. Then add 1g of polyvinyl pyrrolidone (PVP) with an average molecular weight of 1,300,000 to the above solution, and continue stirring for 2 hours to ensure that the solution is evenly mixed. After stirring, a blue transparent viscous liquid is formed. After that, the viscous liquid after stirring is added to the electrospinning syringe, the needle voltage applied is 18kV, the distance between the needle and the spinning collector is 20cm, and the syringe propulsion speed is 0.6mL / min.

[0040] In this step, Ce(NO3)2·6H2O and Cu(NO3)2·3H2O are the precursors of Ce element and Cu element respectively. The mass of Cu(NO3)2·3H2O is determined according to the molar ratio of Ce element to Cu element. The molar ratio of Ce element to Cu element in this embodiment is 5:1.

[0041] (2) Calcination synthesis of nanotube materials

[0042] After the electrospinning is completed, the nanofibers are removed and placed in a porcelain boat, which is then calcined in a tube furnace at 600°C for 2 hours at a heating rate of 1°C / min. After the calcination is completed and the mixture returns to room temperature, the synthesized light yellow Cu-doped CeO2 nanotubes are taken out and named Ce / Cu-5.

[0043] Example 2

[0044] A method for preparing a copper-doped cerium oxide gas-sensitive material, the specific steps are as follows:

[0045] (1) Preparation of nanofibers by electrospinning

[0046] First, a mixed solution of ethanol and dimethylformamide (DMF) was prepared, in which the volume ratio of ethanol to DMF was 3:2. Take 0.6g of cerium nitrate hexahydrate (Ce(NO3)2·6H2O) and 0.1675g of copper nitrate trihydrate (Cu(NO3)2·3H2O), add 10mL of the prepared mixed solution of ethanol and DMF, and then stir magnetically at room temperature for 30 minutes at a speed of 1000r / min to fully dissolve the material and finally form a blue transparent solution. Then, 1g of polyvinyl pyrrolidone (PVP) with an average molecular weight of 1,300,000 was added to the above solution, and stirring was continued for 2 hours to ensure that the solution was evenly mixed. After stirring, a blue transparent viscous liquid was formed. After that, the viscous liquid after stirring was added to the electrospinning syringe, the voltage applied to the needle was 18kV, the distance between the needle and the spinning collector was 20cm, and the syringe propulsion speed was 0.6mL / min.

[0047] In this step, Ce(NO3)2·6H2O and Cu(NO3)2·3H2O are the precursors of Ce element and Cu element respectively. The mass of Cu(NO3)2·3H2O is determined according to the molar ratio of Ce element to Cu element. The molar ratio of Ce element to Cu element in this embodiment is 2:1.

[0048] (2) Calcination synthesis of nanotube materials

[0049] After the electrospinning is completed, the nanofibers are removed and placed in a porcelain boat, which is then calcined in a tube furnace at 600°C for 2 hours at a heating rate of 1°C / min. After the calcination is completed and the mixture returns to room temperature, the synthesized light yellow Cu-doped CeO2 nanotubes are taken out and named Ce / Cu-2.

[0050] Example 3

[0051] A method for preparing a copper-doped cerium oxide gas-sensitive material, the specific steps are as follows:

[0052] (1) Preparation of nanofibers by electrospinning

[0053] First, a mixed solution of ethanol and dimethylformamide (DMF) was prepared, in which the volume ratio of ethanol to DMF was 3:2. Take 0.6g of cerium nitrate hexahydrate (Ce(NO3)2·6H2O) and 0.335g of copper nitrate trihydrate (Cu(NO3)2·3H2O), add 10mL of the prepared mixed solution of ethanol and DMF, and then stir magnetically at room temperature for 30 minutes at a speed of 1000r / min to fully dissolve the material and finally form a blue transparent solution. Then add 1g of polyvinyl pyrrolidone (PVP) with an average molecular weight of 1,300,000 to the above solution, and continue stirring for 2 hours to ensure that the solution is evenly mixed. After stirring, a blue transparent viscous liquid is formed. After that, the viscous liquid after stirring is added to the electrospinning syringe, the needle voltage applied is 18kV, the distance between the needle and the spinning collector is 20cm, and the syringe propulsion speed is 0.6mL / min.

[0054] In this step, Ce(NO3)2·6H2O and Cu(NO3)2·3H2O are the precursors of Ce element and Cu element respectively. The mass of Cu(NO3)2·3H2O is determined according to the molar ratio of Ce element to Cu element. The molar ratio of Ce element to Cu element in this embodiment is 1:1.

[0055] (2) Calcination synthesis of nanotube materials

[0056] After the electrospinning is completed, the nanofibers are removed and placed in a porcelain boat, which is then calcined in a tube furnace at 600°C for 2 hours at a heating rate of 1°C / min. After the calcination is completed and the mixture is restored to room temperature, the synthesized light yellow Cu-doped CeO2 nanotubes are taken out and named Ce / Cu-1.

[0057] Example 4

[0058] A method for preparing a copper-doped cerium oxide gas-sensitive material, the specific steps are as follows:

[0059] (1) Preparation of nanofibers by electrospinning

[0060] First, a mixed solution of ethanol and dimethylformamide (DMF) was prepared, in which the volume ratio of ethanol to DMF was 1:1. Take 0.6g of cerium nitrate hexahydrate (Ce(NO3)2·6H2O) and 0.335g of copper nitrate trihydrate (Cu(NO3)2·3H2O), add 10mL of the prepared mixed solution of ethanol and DMF, and then stir magnetically at room temperature for 30 minutes at a speed of 1000r / min to fully dissolve the material and finally form a blue transparent solution. Then add 1g of polyvinyl pyrrolidone (PVP) with an average molecular weight of 1,300,000 to the above solution, and continue stirring for 2 hours to ensure that the solution is evenly mixed. After stirring, a blue transparent viscous liquid is formed. After that, the viscous liquid after stirring is added to the electrospinning syringe, the voltage applied to the needle is 15kV, the distance between the needle and the spinning collector is 15cm, and the syringe propulsion speed is 0.2mL / min.

[0061] In this step, Ce(NO3)2·6H2O and Cu(NO3)2·3H2O are the precursors of Ce element and Cu element respectively. The mass of Cu(NO3)2·3H2O is determined according to the molar ratio of Ce element to Cu element. The molar ratio of Ce element to Cu element in this embodiment is 1:1.

[0062] (2) Calcination synthesis of nanotube materials

[0063] After the electrospinning is completed, the nanofibers are removed and placed in a porcelain boat, which is then calcined in a tube furnace at 400°C for 4 hours at a heating rate of 0.5°C / min. After the calcination is completed and the mixture is restored to room temperature, the synthesized light yellow Cu-doped CeO2 nanotubes are taken out.

[0064] Comparative Example 1

[0065] On the basis of Example 1, different from Example 1, copper nitrate trihydrate is not added, and a pure phase CeO2 nanotube material is synthesized, which is named CeO2.

[0066] (1) Crystal form analysis

[0067] The materials in Examples 1-3 were subjected to XRD phase analysis. Figure 1As shown. It can be observed that CeO2 and Ce / Cu-5, Ce / Cu-2, Ce / Cu-1 samples have obvious diffraction peaks at 28.3°, 32.9°, 47.2° and 56.0°, corresponding to the (111), (200), (220) and (311) crystal planes of cubic fluorite CeO2, respectively. Compared with pure phase CeO2, the crystal form of Ce / Cu-5, Ce / Cu-2, Ce / Cu-1 samples has not changed, indicating that they have good stability. Moreover, with the increase of Cu doping amount, CuO is generated in Cu-doped CeO2 samples, which can improve the conductivity of sensitive materials.

[0068] (2) Morphological analysis

[0069] The morphology of the Ce / Cu-5 material in Example 1 was analyzed by SEM. Figure 2 It can be observed that Ce / Cu-5 presents a hollow nanotube structure, and the nanotubes are uniform in size with a diameter of about 10 nm.

[0070] (3) Elemental analysis

[0071] The element distribution analysis of the Ce / Cu-5 material morphology in Example 1 is as follows: Figure 3 It can be observed that the elements in Ce / Cu-5 are evenly distributed, and the distribution of Ce and Cu elements overlaps, indicating that the contact between Cu atoms and Ce atoms is close.

[0072] (4) Oxygen vacancy research

[0073] The morphology of CeO2 in Comparative Example 1 and Ce / Cu-5 in Example 1 was characterized by Raman spectroscopy. Figure 4 In both materials, it can be observed that the -1 The characteristic peaks of CeO2 2g Vibrational modes and oxygen vacancies (O V In addition, compared with the CeO2 of Comparative Example 1, the oxygen vacancy characteristic peak intensity of the Ce / Cu-5 material of Example 1 is higher, which means that more oxygen vacancies are created in CeO2 after Cu doping CeO2.

[0074] (5) Gas-sensing performance analysis

[0075] The material synthesized in the embodiment is deposited on the sensing element to prepare the sensor and then a dynamic test and result analysis are performed. The specific steps are as follows:

[0076] Preparation of sensors

[0077] The samples synthesized in Examples 1-3 were placed in an agate mortar and ground thoroughly, and then a certain amount of deionized water was added and stirred to form a slurry material. Then, a brush was used to apply the slurry material to the interdigital electrode area of ​​the MEMS sensor element, and dried in a 60°C oven for 2 hours. The MEMS sensor element uses the HHC1000 micro-hotplate chip of Hefei Micro-Nano Sensing Technology Co., Ltd., which integrates a micro heater and interdigital electrodes, and has the advantages of low power consumption and high reliability.

[0078] Sensor test method:

[0079] The sensor is tested dynamically, and the H2S gas concentration is controlled by adjusting the flow ratio of standard H2S gas and background gas through a gas flow meter. Conventional background gas is compressed dry air, in which the volume ratio of N2 is 78% and the volume ratio of O2 is 22%. In order to produce background gas with different oxygen contents, the ratio of compressed dry air and high-purity nitrogen (99.999%) is adjusted by a flow meter, and background gas with oxygen contents of 22%, 11%, 5.5%, 2.75%, and ~0% can be prepared.

[0080] Gas Sensing Performance Analysis

[0081] like Figure 5 As shown, the sensor responds to H2S at different temperatures, where the response is defined as R a / R g , where R a and R g are the stable resistance values ​​of the sensor in background gas and H2S gas, respectively. It can be seen that the optimal operating temperature of Ce / Cu-5, Ce / Cu-2, and Ce / Cu-1 materials obtained in Examples 1-3 is 260°C, which is lower than 273°C of CeO2 material, indicating that Cu doped CeO2 can effectively reduce the working temperature of the material. Moreover, Ce / Cu-5 exhibits the highest response and can be regarded as the best proportion of Cu doped CeO2 nanotube material.

[0082] like Figure 6 As shown, compared with CeO2, the selectivity of Ce / Cu-5 for H2S is effectively enhanced.

[0083] like Figure 7 As shown in the figure, as the H2S concentration increases, the Ce / Cu-5 response value also increases, and the material can still detect H2S at 100 ppb.

[0084] like Figure 8As shown in the figure, the response / recovery curve of the Ce / Cu-5 sensor prepared in the present invention, the response time is defined as the time required for the response to increase by 90% after the response contacts the gas, and the recovery time is defined as the time required for the response to decrease by 90% after the response is separated from the target gas. It can be observed from the figure that the gas-sensitive material of the present invention has a good response to H2S, and the response / recovery time is short, which is 68s and 9s respectively.

[0085] like Fig. 9 As shown, the dynamic resistance curves of the Ce / Cu-5 sensor prepared by the present invention to H2S under different oxygen content backgrounds show that the sensor exhibits good response-recovery behavior and good repeatability under oxygen content ranging from 22% to 0%.

[0086] like Fig.10 As shown, according to Fig. 9 The curve in the figure calculates the response of the Ce / Cu-5 sensor to H2S at different oxygen contents. It can be found that the response value of the sensor does not decrease with the decrease of oxygen content, indicating that the sensor can still maintain a high sensitivity in a low oxygen environment.

[0087] like Fig.11 As shown, according to Fig. 9 The curve in the figure calculates the response / recovery time of the Ce / Cu-5 sensor to H2S at different oxygen contents. It can be found that as the oxygen content decreases, the response / recovery time of the sensor basically remains at the same order of magnitude, indicating that the sensor maintains a fast response / recovery speed at different oxygen contents.

Claims

1. A method for preparing a copper-doped cerium oxide gas-sensitive material, characterized in that: The following steps are involved: (1) adding cerium salt and copper salt to a mixed solution of ethanol and DMF or ethanol and deionized water, stirring to form a transparent solution; (2) adding PVP to the above solution and stirring to form a viscous liquid; (3) electrospinning the viscous liquid to obtain nanofibers; (4) Calcinate the nanofibers to obtain Cu-doped CeO2 nanotubes.

2. The method for preparing a copper-doped cerium oxide gas-sensitive material according to claim 1, characterized in that: In step (1), the molar ratio of Ce element to Cu element is 1:1 to 5:

1.

3. The method for preparing a copper-doped cerium oxide gas-sensitive material according to claim 1, characterized in that: In step (1), cerium salt and copper salt are added to a mixed solution of ethanol and DMF.

4. The method for preparing the copper-doped cerium oxide gas-sensitive material according to claim 3, characterized in that: In step (1), the volume ratio of ethanol to DMF is 1:1 to 3:

2.

5. The method for preparing the copper-doped cerium oxide gas-sensitive material according to claim 1, characterized in that: In step (4), the calcination temperature is 400-600° C. and the calcination time is 2-4 hours.

6. The method for preparing the copper-doped cerium oxide gas-sensitive material according to claim 1, characterized in that: In step (4), the heating rate of the calcination is 0.5 to 5°C / min.

7. The method for preparing a copper-doped cerium oxide gas-sensitive material according to claim 1, characterized in that: In step (3), the parameters of the electrospinning are: the voltage applied to the needle is 15 to 20 kV, the distance between the needle and the spinning collector is 15 to 20 cm, and the syringe propulsion speed is 0.2 to 0.6 mL / min.

8. A gas sensor, characterized in that: The gas sensitive material used includes the copper-doped cerium oxide gas sensitive material prepared by the method according to claim 1.

9. Use of the copper-doped cerium oxide gas-sensitive material prepared by the method according to claim 1 in detecting H2S gas.